The relationship between certain fitness elements and performance level and achievement in the long jump under 20 years old - Jassim, Asst.L. Ahmed Sabah Abdul; Saleh, Asst.L. Adhraa Sadiq; Al-Hussein, Asst.L. Fatima Abbas Ali (Sulaimani Journal for Humanities, 2026)
The Relationship Between Some Physical Fitness Elements and Performance Level and Achievement in the Long Jump Under 20 Years Old Chapter One included an introduction to the research and its importance, as well as the research problem, which states: (Through the researchers' monitoring of the performance level of long jumpers in Karbala Governorate under 20 years old, it was found that they did not achieve good results in past championships. From this, they felt that there was a training problem among the jumpers and wanted to diagnose the weakness that led to the performance level not being at the required level. Therefore, the researchers resorted to solving the problem by conducting some tests for physical fitness elements (maximum speed, leg muscle strength, abdominal muscle strength). From this, the researchers aim to delve into this experience to determine the physical elements that contribute to raising the athlete's efficiency in reaching the level of achievement in this competition, as well as to contribute to supporting and enhancing the training process in the governorate and the country through research and investigation in this field. This chapter also included the spatial, temporal, and human aspects. Chapter Two included the research methodology, the statistical methods, and the tests that were developed. Chapter Three included the research results, and Chapter Four included the research recommendations and conclusions.